INTERACTIONS BETWEEN TEST DURATION AND CANDIDATES’ PERFORMANCE IN ACADEMIC SELECTION APTITUDE TESTS AMONG STUDENTS IN UASIN GISHU COUNTY, KENYA - Gabriel, Chege Kimani (European Scientific Journal, ESJ, 2015)
According to Kenya’s Institute of Policy Analysis and Research (2008), there is poor management of national examinations. Cases of cheating in national examinations due to poor management of the processeswhere leaked papers give some students and schools an unfair advantage over others – have become commonplace. Yet, placement to university is based om national exams. Developed countries use aptitude tests to make placement decisions. Such tests may be proposed for adoption in Kenya but only after establishing their relevance. The purpose of the study was to determine the possible relevance of such tests and in this particular study the researcher sought to find out whether the test duration had a significant effect on the candidate’s performance in the Scholastic achievement test among Kenyan students. The null hypothesis HO: Test duration has no significant effect on the candidate’s performance in the Scholastic achievement test was tested. The study adopted the causal-comparative design. The target population comprised all the 2469 form four students in the twenty four (24) secondary schools in Eldoret town from which eight (8) schools were sampled using the stratified random sampling technique and a sample of 240 students was selected purposively from the eight (8) schools. The data was collected using a past Scholastic Achievement Test. The study data was analysed using ANOVA and it was conducted using SPSS 17 version 22 with the level of significance being α = 0.05. The findings indicated that test duration has no significant effect on the examinee’s performance in the Scholastic achievement test. The implication is that taking the SAT for longer or shorter than the prescribed time (225 minutes) does not significantly advantage or disadvantage the examinees by changing their performance in the SAT. Concerning the test taking duration, the study recommends that the examinees be allowed enough time as possible when taking the aptitude test since time has no significant effect on the examinee’s performance in the SAT.